2021
DOI: 10.1021/acsaem.1c02604
|View full text |Cite
|
Sign up to set email alerts
|

Advances and Challenges in Industrial-Scale Water Oxidation on Layered Double Hydroxides

Abstract: A substantial effort is devoted to the development of efficient electrolyzers made of earth-abundant elements for low-temperature industrial-scale water electrolysis. However, a large current density leads to the decline of the reaction kinetics that result from the decrease of local pH, the irreversible redox states of active metal sites, and the structure and composition collapse. Currently, the transition metal layered double hydroxides (LDHs) are proven as efficient alkaline oxygen evolution catalysts and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 234 publications
(487 reference statements)
0
16
0
Order By: Relevance
“…5a), which surpasses most transition metal-based OER catalysts recently reported for seawater electrolysis (Table S5, ESI†) and alkaline water oxidation in general. 39,44 The slightly increased potential after continuous operation for several hundred hours was due to the drift of potential of the Hg/HgO reference electrode at extremely high pH. After refreshing the reference electrode, the potential returned to the initial value and the polarization curves almost completely overlap with the initial state (Fig.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…5a), which surpasses most transition metal-based OER catalysts recently reported for seawater electrolysis (Table S5, ESI†) and alkaline water oxidation in general. 39,44 The slightly increased potential after continuous operation for several hundred hours was due to the drift of potential of the Hg/HgO reference electrode at extremely high pH. After refreshing the reference electrode, the potential returned to the initial value and the polarization curves almost completely overlap with the initial state (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…However, the Tafel slope was increased to 40.2 mV dec −1 in the absence of Fe( ii ) ions in the alkaline seawater, indicating the OER kinetics was significantly hindered, probably due to the loss of Fe active centers which is promoted by the formation of various soluble Fe complexes in highly alkaline electrolytes. 39 The electrochemical impedance spectroscopy (EIS) was measured in Fig. 3d and the spectra were fitted using the equivalent circuit shown in the inset.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, external forces such as supergravity, magnetic, and ultrasonic fields can be utilized during water electrolysis to moderate the bubble size and enhance the bubbles’ separation rate by inducing convection on the electrolyte [313,314] . Through the use of high‐speed imaging, a recent study demonstrated how ultrasound affects the diameter and velocity of bubbles during HER [331] .…”
Section: Strategies In Enhancing Catalytic Performancementioning
confidence: 99%
“…To minimize the damage caused by metal dissolution, oxidation-or reduction-induced redeposition can be exploited to regenerate electrocatalysts completely or partially. [313] For instance, a study showed SEM images of patchy FeNiO x films with exposed FTO surfaces due to the dissolution of iron from the films after being subjected to electrolysis. [330] The solubilized Fe species redeposited on the hydrogen-evolving cathode at HCD as a concurrent reaction to HER.…”
Section: Dissolution Of Active Sitesmentioning
confidence: 99%
“…Despite possessing such exceptional properties, their phase stabilization remains a critical issue which requires long reaction processes. , Therefore, an optimization is required in order to have a stable phase with good electrical conductivity (which remains low for LDHs) for faster redox kinetics at their surface-active sites . Alongside, in LDHs, it has been observed that ion transport kinetics remains sluggish due to the absence of sufficient transport channels leading to high ion migration resistance. , This will lead to underutilization of surface and bulk active sites, and thus, redox kinetics remains low.…”
Section: Introductionmentioning
confidence: 99%